(untitled) (American Journal of Pedagogical and Educational Research, 2024)
From the analysis of the distribution of hours allocated to classes of different forms in the study of physics in technical specialties of higher educational institutions, it turns out that modeling sessions can be carried out in accordance with the hours allocated for the implementation of practical classes. The allocated hours indicate that the proposed approaches to organizing practical training on solving a system of theoretical issues can be used in teaching students to model original objects.